2013
DOI: 10.5581/1516-8484.20130120
|View full text |Cite
|
Sign up to set email alerts
|

Chronic myeloid leukemia: an overview of the determinants of effectiveness and therapeutic response in the first decade of treatment with imatinib mesylate in a Brazilian hospital

Abstract: BackgroundIn the last decade, there has been a revolution in chronic myeloid leukemia treatment with the introduction of tyrosine kinase inhibitors with imatinib mesylate becoming the frontline therapy. ObjectiveTo evaluate the therapeutic efficacy of imatinib mesylate in treating chronic myeloid leukemia patients and to identify factors related to therapeutic efficacy. MethodsThis retrospective study was based on information obtained from patients' records in the Hematology Service of Hospital Universitário W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
(25 reference statements)
0
5
0
Order By: Relevance
“…Importantly, we were able to examine clinical outcomes (progression and mortality), in contrast to prior studies that mainly examined molecular response. [5][6][7][8][9][10][11][12]16,19,20 As all KPSC patients had pharmacy medication coverage, we could study outcomes without the confounding effects of variable insurance coverage. For example, a previous case series report from Brazil showed that patients with much lower adherence (because of lack of access to drugs) correlated with a low cytogenetic and molecular response.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, we were able to examine clinical outcomes (progression and mortality), in contrast to prior studies that mainly examined molecular response. [5][6][7][8][9][10][11][12]16,19,20 As all KPSC patients had pharmacy medication coverage, we could study outcomes without the confounding effects of variable insurance coverage. For example, a previous case series report from Brazil showed that patients with much lower adherence (because of lack of access to drugs) correlated with a low cytogenetic and molecular response.…”
Section: Discussionmentioning
confidence: 99%
“…Among the 14 studies analyzed, seven referred only to adherence, one referred only to discontinuation, five assess adherence and discontinuation and one included only suboptimal adherers. It was evident that few studies have assessed the achievement of cytogenetic and molecular response, which are important parameters for analyzing the absence of Philadelphia chromosome, as well as reduced levels of BCL-ABL rearrangement (Marin et al, 2010;Cid et al, 2013;Reis et al, 2013). In addition, four studies showed adherence rates relatively low to imatinib, such as between 19.0 and 53.0%.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, four studies showed adherence rates relatively low to imatinib, such as between 19.0 and 53.0%. It has been shown in clinical trials that reduced adherence rates are associated with lower rates of CCR and CMR (Marin et al, 2010;Cid et al, 2013). In the clinical context, several factors may influence adherence to treatment regimens and these include not only those aspects of the treatment, but also patient characteristics (Partridge et al, 2002;Efficace et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This issue of the Revista Brasileira de Hematologia e Hemoterapia carries an article entitled "Chronic myeloid leukemia: an overview of the determinants of effectiveness and therapeutic response in the first decade of treatment with imatinib mesylate in a Brazilian hospital" which states that only 20% of CML patients, most in the chronic phase, had a good response to imatinib therapy ( 2 ) . The authors correlated this low outcome to several variables, including delay to start treatment, the advanced stage of the disease, poor access to medication and lack of proper monitoring, such as cytogenetic and molecular analyses.…”
mentioning
confidence: 99%